1997
DOI: 10.1177/096032719701600904
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental passage of aluminium from pregnant mice to fetus organs after maternal transcutaneous exposure

Abstract: Aluminium is present in tap water, antiperspirants and cosmetics up to 20%. Teratogenicity of aluminium was clearly identified after per os or intravenous administra tion. Malformations and other alterations by aluminium intoxication were evaluated in fetus. In the present study, we investigated the possible transplacental passage of aluminium and its accumulation in the tissue after cutaneous uptake. Female Swiss mice received alumi nium chloride by cutaneous way (0.4 μg/day) during 20 days of gestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…In our research this phenomenon was present in the F 0 and F 1 generations, but in the F 2 generation was absent, even at 200 ppb AS, denoting, in our opinion, a lack of hypophysis response, and confirming others authors' results who proved that aluminium after absorption passes easily through the rat placenta and via milk in the suckling period, and so can be found in the next generation's tissues and organs (41,42).…”
Section: Discussionsupporting
confidence: 91%
“…In our research this phenomenon was present in the F 0 and F 1 generations, but in the F 2 generation was absent, even at 200 ppb AS, denoting, in our opinion, a lack of hypophysis response, and confirming others authors' results who proved that aluminium after absorption passes easily through the rat placenta and via milk in the suckling period, and so can be found in the next generation's tissues and organs (41,42).…”
Section: Discussionsupporting
confidence: 91%
“…The skin is no barrier to aluminium absorption (Exley, 1998). Experiments with shaved adult mice, naked mouse pups and excised skin patches taken from adult mice have all shown that topically applied aluminium salts can be absorbed through mouse skin (Anane et al, 1995(Anane et al, , 1997. Furthermore, dermal absorption of aluminium could be detected in human subjects from a single application of aluminium chlorhydrate using the isotope 26 Al as the tracer (Flarend et al, 2001).…”
Section: Agents That Damage Dnamentioning
confidence: 97%
“…Whilst it had been assumed that unbroken skin would be an effective barrier to transdermal uptake of aluminium, dermal absorption of topically applied antiperspirant aluminium salts has now been demonstrated through intact mouse skin [25,26] and human skin [27][28][29][30]. Dermal absorption of aluminium was detected in human subjects from a single application of aluminium chlorhydrate using the isotope 26 Al as the tracer [27].…”
Section: The Case For An Involvement Of Aluminium Saltsmentioning
confidence: 99%